Aeromonas chitinase degrades chironomid egg masses. Issue 1 (21st December 2015) - Laviad, Sivan; Golan, Amnon; Shaked, Tamar; Vaizel‐Ohayon, Dalit; Halpern, Malka; Pick, Elah
Summary: Chironomids are freshwater insects that undergo a complete metamorphosis of four life stages. Chironomid egg masses can be degraded by V ibrio cholerae and some A eromonas species. Egg mass degradation by V . cholerae requires haemagglutinin protease activity. Our aim was to identify the egg mass degrading (EMD) factor secreted by A eromonas dhkanesis 3K1C15. Following the hypothesis that the EMD factor of A . dhkanesis is also a protease, secreted proteases were screened, but none of them proved to have the same properties as the EMD factor. Using conventional protein purification methods, we found that the active fraction included chitinases. We further confirmed chitin as a building block of the egg masses. Interestingly, by supplementing bacterial growth media with chitin, we observed unexpected EMD factor activity in A eromonas isolates that initially were not able to degrade egg masses. Accordingly, we concluded that although strain 3K1C15 secretes chitinases constitutively, most A eromonas strains secrete chitinases inductively. Induction of chitinases in nature presumably occurs when bacteria are attached to the egg mass habitat, in which chitin is abundant. Considering that chitinases are highly conserved across bacteria phyla, we assume that the role of this enzyme in the bacteria–insect interplay could be wider than is currently thought.